Understanding the Crystallization Mechanism of a Wollastonite Base Glass Using Isoconversional, IKP Methods and Master Plots - Perez, Juan M.; Teixeira, Silvio R. [UNESP]; Rincon, Jesus Ma.; Romero, Maximina (Wiley-Blackwell, 2012)
The complex development of crystals found in the crystallization of SiO2-Al2O3-CaO-Na2O glass has been explained using Differential Thermal Analysis. The crystal growth process has been studied using isoconversional, invariant kinetic parameters, and master plots methods. The applied kinetic models have revealed activation energy values that are over 360 and 385 kJ/mol by employing the integral and differential kinetic methods, respectively. The crystallization process schedule that was previously observed using scanning electron microscopy has been corroborated in this study using the kinetic methods. The crystallization of wollastonite occurs through a complex two-stage mechanism, with early three-dimensional growth of crystals (A(3) mechanism) on the surface of glass particles followed by one-dimensional growth of needles (A(3/2) mechanism) toward the interior of grains. The results presented in this article are in agreement with a previous paper that employed the Kissinger non-isothermal method and the Ligero approximation.